Economics of the system of long-term care for senior citizens - I. I. Deren; K. A. Samofatova (Вестник университета, 2023)
The article is devoted to the study of the system of long-term care for senior citizens. The purpose of the article is to analyze the current state of the sphere of social services of the population, as well as to consider the essence, tasks, advantages and disadvantages of the introduction of a long–term care system on the territory of Russian Federation. According to the study results, the authors conclude that the introduction and development of a system of longterm care for senior citizens is one of the foreground and socially significant tasks of Russian Federation. The authors propose to use public-private partnership as one of the tools to provide senior citizens with the necessary level of availability of qualified and permanent assistance in the long-term care system. In the process of writing the article, the authors used such research methods as analysis, synthesis, a systematic approach, methods of displaying and processing the information received.